Calculation of the circular-polarization P3 Stokes parameter for electron-silver scattering - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2013)
We present relativistic convergent close-coupling (RCCC) calculations of the P3 circular light polarization. Stokes parameter for atomic silver associated with the radiative decay of the electron-impact excited (4d105p) 2P3/2 state. The results are compared with the recent measurements of Jhumka et al. [Phys. Rev.A 87, 052714 (2013)]. We find excellent agreement between the RCCC results and experiment across the full energy range of measurements. We also find that relativistic effects have a weak influence on the calculation of P3 in the energy range considered.